Impact of simulation training on communication skills and informed consent practices in medical students- a randomised controlled trial - Cathleen A. McCarrick; Alice Moynihan; Philip D. McEntee; Patrick A. Boland; Suzanne Donnelly; Helen Heneghan; Ronan A. Cahill (BMC Medical Education)
Abstract Aims Communication skills are essential for surgeons; typified regarding consent. We evaluated communication simulation training (CST) for informed consent competency in senior medical students. Methods With institutional ethics approval, CST was implemented during our undergraduate clinical surgery module. Students were divided in two groups by randomized cluster sampling and assessed at baseline on consent competency using a simulated patient (SP) for a colonoscopy scenario. The control group proceeded with standard clinical learning, while the intervention group received CST, which included tutor-led roleplay of good and poor consent for laparoscopic cholecystectomy, followed by peer reenactment and discussion. All students then underwent repeat assessment—an observed SP consent for laparoscopic appendicectomy—by an independent, single-blinded senior clinician within the same week. Communication skills were scored by Objective Structured Clinical Examination (OSCE) using both the University College of Dublin School of Medicine OSCE scoring rubric and the externally validated Global Communication Rating Scale (GCRS). Intervention group students were surveyed including anonymously reporting consent confidence pre- and post-CST. All procedures chosen are the three most commonly witnessed by students within their surgical rotations and all are typically familiar with them at this stage in their training. Results Of the 122 students who participated, 61 received Communication Skills Training (CST). Baseline UCD and GCRS scores were similar across groups, but post-intervention scores were significantly higher in the CST group. Their average grade improved from a C to a B+, with a medium to large effect size (0.79), while the control group remained at a C. CST students also showed significant gains in GCRS domains—initiation, verbal communication, session structuring, and information relay. Self-confidence improved notably: only 11 students initially felt confident obtaining consent, compared to 62 post-training, with over 80% survey response rate. Conclusions Medical student CST improves consent communication skills versus observational learning demonstrating its impactful role within clinical undergraduate training. Clinical trial number ISRCTN10251799. Trial registration date 31.10.24.